If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-14x-11=11x-14
We move all terms to the left:
-14x-11-(11x-14)=0
We get rid of parentheses
-14x-11x+14-11=0
We add all the numbers together, and all the variables
-25x+3=0
We move all terms containing x to the left, all other terms to the right
-25x=-3
x=-3/-25
x=3/25
| r/2-7=-4 | | -5(x-3)+9x=35 | | 3(2x+1)+x=7+3x | | y=14/2 | | 5x*(-10)=-20 | | (14x+39)+(6x+79)=180 | | x2-7x+14=2 | | 1/4x-2=21 | | y^2+7y-60=0 | | m+2-3=5m+8 | | 108+(13x-45)=180 | | 141+x=180 | | 5x+6=2x+50 | | -9.3=(x/5)+3.2 | | -19+1/3n=-22 | | 26^9x+5=-1 | | 1/3(12x-3)=7 | | 5/6×n=10 | | 2/5=-5x | | 2/s=16 | | 15y-3=25 | | 150−9x=78-x | | 4x=8^2x-2 | | (3x)()=12x2 | | 8^2+x^2=12^2 | | 4x=82x-2 | | 7x+22=99 | | 8^2+b^2=12^2 | | P/2=p+5/10 | | 67+63+x=180 | | 1/3(y-6=y | | 0.333(4a+1)=0.5a |